Foreign divestment: What stays when multinationals leave? - Wolfgang Sofka; Miguel Torres Preto; Pedro de Faria (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2015)
When an MNE closes its doors, workers may find themselves in demand or struggling, depending on the nature of their employment and the characteristics of the foreign affiliate itself. The authors recommend a targeted policy approach that focuses on transition assistance for the most vulnerable employees.
Keywords: 330